Integrative Analysis Identifies Cell-Type-Specific Genes Within Tumor Microenvironment as Prognostic Indicators in Hepatocellular Carcinoma - Huang, Zi-Li; Xu, Bin; Li, Ting-Ting; Xu, Yong-Hua; Huang, Xin-Yu; Huang, Xiu-Yan (Frontiers in Oncology, 2022)
Background: Hepatocellular carcinoma (HCC) is a leading cause of cancer-related mortality worldwide, but still lacks effective early screening and prognostic assessment methods. Methods: The Cox regression model was built to stratify the HCC patients. The single-cell RNA sequencing data analysis and gene set enrichment analysis were used to investigate the biological function of the markers. Overexpression or knockdown, quantitative Real-Time PCR, and immunohistochemistry assay were conducted to validate the biological function. Results: In this study, we developed a predictive model with optimized markers for HCC recurrence. Specifically, we screened out 8 genes by a series of data analyses, and built a multivariable Cox model based on the 8 genes. The risk stratification by the Eight-Gene Cox (EGC) model was closely associated with the recurrence-free survival (RFS) in both training and the two validation cohorts. The independence and superiority of the EGC model have been demonstrated. Moreover, we also investigated the cell type specific expression patterns of the eight recurrence-related genes in tumor microenvironment by single-cell RNA sequencing data, and interpreted their functionalities by correlation and gene set enrichment analysis. Particularly, PLCB1 and SLC22A7 were predominantly expressed in malignant cells, and were predicted to promote angiogenesis and maintain the normal metabolism in liver, respectively. In contrast, both FASLG and IL2RB were specifically expressed in T cells, and were highly correlated with T cell marker genes, suggesting that the two genes might maintain normal function of T cell mediated immune response in tumor tissues. Conclusion: The EGC model and eight marker genes could not only accurately predict the HCC recurrence, but also improve our understanding of their functionalities in HCC recurrence.